A case study of wind turbine loads and performance using steady-state analysis of BEM. Issue 1 (2nd January 2021) - Bhargava, Vasishta; Kasuba, Sainath; Maddula, Satya Prasad; Jagadish, Donepudi; Khan, Md Akhtar; Padhy, Chinmaya Prasad; Chinta, Hari Prasad; Chekuri, Chandra Sekhar Verma; Dwivedi, Yagya Dutta
ABSTRACT: Wind power plants produce energy by utilising the kinetic energy available from wind. Turbine blades undergo millions of revolution during lifetime and subjected to wear and tear due to unsteady aerodynamic forces. In this work, steady-state blade element momentum computations were performed for horizontal axis 2.1 MW wind turbine to evaluate aerodynamic loads and performance. Axial and tangential loads along the blade span were found to increase near the outboard stations of blade but reduced towards tip. Turbine performance parameters viz. thrust and torque coefficients for tip speed ratio range of 5.1–9.5 showed that maximum values are found as 0.95, 0.98 and 0.12, 0.18 for 0 0 and 10 0 yaw angles and agreed well with SCADA data used for validation. GRAPHICAL ABSTRACT: